The encounter of God and man in the trial of Jesus : an exegetical investigation of Jn 18, 28-19, 16a - Zabala, Artemio, 1938- (1980)
The Passion narrative proper in the gospel according to Jn (=Chs 18 and 19) divides itself neatly into three clear parts. Part I. (Jn 18, 1-27) consists of the story of Jesus' arrest (Jn 18, 1-12) and his hearing before Annas (Jn 18, 13-27). Part II (Jn 18, 28-19, 16a) consists of Jn's version od the trial of Jesus before the Roman prefect Pontius Pilate. Part III (Jn 19, 16b-42), which directly precedes the Johanine presentation of the risen Jesus (Jn 20), consists of Jn's account of the crucifixion, the death and the burial. The focus of theis present study is on Part II of the Johanine Passion. Because of the nature of Jn's composition and thought, it will be necessary, however, to refer constantly to the wider context of the trial in the passion as it will be avoidable to make references to the Book of signs, as the first half of the fourth gospel is commonly called. Unfortunately, a thorough study of such passages as will be referred to outside our focus of attention is an undertaking which time does not allow us to attempt at present.
Inaugural--Dissertation zur Erlangung der Wurde eines Doktors der Evangelisch-Theologischen Facultat der Ruprecht-Karl Universitat
Dissertation (D.Th) -Ruprecht-Karl Universitat, Heildelberg